Scale-independent description of the rigid-body penetration of spherical projectiles into semi-infinite adobe targets. (January 2015) - Heine, A.; Wickert, M.
Abstract: In impact experiments, the penetration depth of spherical projectiles into semi-infinite adobe targets has been investigated. In total, 20 tests were performed with steel projectiles of diameters 7.5, 10.0 and 13.5 mm in the velocity regime from 240 to 3230 m/s. In addition, 2 single experiments with aluminum and titanium projectiles were conducted at impact velocities of 830 and 920 m/s, respectively. After an appropriate normalization, all penetration depth vs. velocity data up to impact velocities of around 1500 m/s can be described by one linear curve. This is the velocity regime where projectile fragmentation does not yet occur. The observed linear relation is discussed in the context of a recently published analytical model and shows the scalability of penetration tests also for the considered adobe target material of low strength and low density. Highlights: Experimental data for the penetration of spherical projectiles into semi-infinite adobe targets is presented and analyzed. The impact velocities were varied in between 240 and 3230 m/s for projectiles of different diameter and material. In the regime where rigid-body penetration persists, the penetration depth is a linear function of the impact velocity. The observed behavior is understood based on a recently published analytical model from a different application context. It is concluded that the rigid-body penetration into adobe is scalable.